Análise da interferência do transporte intermunicipal de passageiros na mobilidade urbana. Estudo de caso: cidade de Pau dos Ferros – RN - Santos Júnior, Elson dos (Universidade Federal Rural do Semi-Árido, 2018)
The Urban mobility refers to a form of media used by the population to move around in cities. For a good planning of the mobility, it is necessary to have an organization of the territory that is not referring to the use and occupation of the ground, the flow of transport of people and goods, and the means of transport used. In the survey, the vehicles carrying out collective intercity passenger transportation were analyzed, analyzing their stopping points and parking lots, and the surrounding regions bring passengers to the Pau dos Ferros - RN, also signaling the number of trips and the number of passagers are transported per day. The objective of this work is to analyze the interference of intercity passenger transport in the urban mobility of the municipality, as well as to identify the main factors affected by the circulation and parking of vehicles of the intermunicipal system. The study and analysis of intercity passenger transport was published among the drivers of intercity transport at their points of interest in the city of Pau dos Ferros - RN, in order to conduct a qualitative and quantitative research of the system regarding its operational characteristics. In the research carried out at the points of study, the data indicated a total of 109 trips a day in 83 vehicles, transporting a total of 795 passengers a day in search of effort to a city of Pau dos Ferros. The system studied plays an important role through the transportation of passengers, since it is incontestable that the surrounding small towns have access to education, commerce and health services, among others, that are offered by the city under study, bringing a relevant return to the local economy. This system of intermunicipal transport is absent due to the absence of regulated passenger transport, which it performs as trips between cities as evidenced by the research. The concept of process was characterized as a situation of insecurity regarding the existence of vehicles for expansion, and, often, with the adulteration of archives with the competent organs.
Artigo Acadêmico
Keywords: Mobilidade urbana; Transporte; Trânsito de passageiros; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA